Agricultural socialized services to stimulate the green production behavior of smallholder farmers: the case of fertilization of rice production in south China - Shi, Fang; Cai, Baozhong; Meseretchanie, Abate; Geremew, Betelhemabraham; Huang, Yuangji (Frontiers in Environmental Science, 2023)
Introduction: This study investigates the impact of Agricultural Socialized Services (ASSs) on the green production behavior (GPB) of smallholder farmers in the main rice production region of southern China. The research aims to address the gap in understanding the relationship between ASSs and the adoption of sustainable agricultural practices by smallholder farmers. Methodology: Data was collected from 741 smallholder farmers in Hunan, Jiangxi, and Zhejiang provinces using a structured questionnaire. A probit model was employed to examine the relationship between ASSs and smallholder farmers’ GPB. Results and Discussion: The study revealed that ASSs have a significant and positive impact on smallholder farmers’ GPB. Farmers who received ASSs tended to adopt more sustainable agricultural practices such as using organic fertilizer and soil-tested formula fertilizer. The findings of this study have important implications for policymakers. The results suggest that policymakers should prioritize the development of services to agricultural producers and strengthen Agricultural Service Systems. This can be achieved through optimizing the public administration service system, establishing joint service organizations, and creating a good financial and legal service environment. By doing so, policymakers can promote the adoption of sustainable agricultural practices and the overall development of the agricultural sector.